Modeling and control strategies of fuzzy logic controlled inverter system for grid interconnected variable speed wind generator - Muyeen, S.M.; Al-Durra, A. (2013)
Today, variable speed operation of a permanent magnet synchronous generator (PMSG) is becoming popular in the wind power industry (PI). A variable speed wind turbine (VSWT)-driven PMSG, in general, is connected to the grid using a fully controlled frequency converter (FC). Along with the generator side converter, the FC necessitates the grid side inverter system that has a great impact on the stability issue of the VSWT-PMSG, especially in the case of network disturbance. The well-known cascaded-controlled inverter system has widely been reported in much of the literature, where multiple PI controllers are used in inner and outer loops. However, a fuzzy logic controller deals well with the nonlinearity of the power system, compared to a PI controller. This paper presents a simple fuzzy logic controlled inverter system for the control of a grid side inverter system, which suits well for VSWT-PMSG operation in a wide operating range. This is one of the salient features of this paper. Detailed modeling and control strategies of the overall system are demonstrated. Both dynamic and transient performances of VSWT-driven PMSG are analyzed to show the effectiveness of the control strategy, where simulation has been done using PSCAD/EMTDC.